2020
DOI: 10.1042/bst20200200
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and the masculinization programming window: human–rodent differences

Abstract: Human male reproductive disorders are common and may have a fetal origin — the testicular dysgenesis syndrome (TDS) hypothesis. In rats, experimentally induced TDS disorders result from disruption of fetal androgen production/action specifically in the masculinization programming window (MPW). MPW androgen action also programs longer anogenital distance (AGD) in male versus female rats; shorter male AGD is correlated with risk and severity of induced TDS disorders. AGD thus provides a lifelong, calibrated read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 94 publications
(182 reference statements)
0
48
0
Order By: Relevance
“…Accordingly, the testosterone level was positively associated with AGD in adult women in the included studies conducted by Wu et al, though this was not confirmed by the included study conducted by Peters et al and the Spanish study group (21,24,26). AGD may be affected not only by intrauterine androgen exposure but also by postnatal hormones, i.e., prenatal androgen exposure may initially dictate the AGD, but postnatal androgen exposure may be required for AGD to grow to the preplanned size (46).…”
Section: Discussionmentioning
confidence: 88%
“…Accordingly, the testosterone level was positively associated with AGD in adult women in the included studies conducted by Wu et al, though this was not confirmed by the included study conducted by Peters et al and the Spanish study group (21,24,26). AGD may be affected not only by intrauterine androgen exposure but also by postnatal hormones, i.e., prenatal androgen exposure may initially dictate the AGD, but postnatal androgen exposure may be required for AGD to grow to the preplanned size (46).…”
Section: Discussionmentioning
confidence: 88%
“…We observed an increased risk of cryptorchidism for exposed pregnancies, which could be due to the hypothesized estrogenic and anti-androgenic activity of LC-PCBs during the 'male programming window' in the rst trimester [59].…”
Section: Previous Literature and Mechanismsmentioning
confidence: 80%
“…Phthalates (33) and bisphenols (34) have been intensively investigated as potential causes of TDS, which has led to their banning by the European Union. However, much of the experimental evidence is on the basis of rodent studies and has been strongly questioned (35), and human studies have had divergent results (36,37). We cannot link the men in the cohorts we studied to any particular environmental exposure, but surely exposure to EDCs was present, to varying degrees, for the entire period of the study.…”
Section: Discussionmentioning
confidence: 95%